Quality of remote teaching in a university context in Esmeraldas-Ecuador, from the teaching experience - Bernabé Lillo, María de los Lirios; González Berruga , Manuel Ángel; Espinoza Ávila, Manuel Eduardo; Armijos Porozo, Irlanda Magali (SATHIRI, 2022)
The pandemic has evidenced the existing inequalities in the countries of the region, and this has rebounded on the Teaching-Learning processes of many children and young people who abruptly stopped attending the classrooms to open up to a new modality of remote teaching. The present study aims to know the experience that university teachers had of remote education and the perception they have about some of the risk factors that students have faced in the Teaching-Learning process during the pandemic. Framed in the interpretive qualitative paradigm, a case study was carried out, with a non-probabilistic sample of eight professors from a private university, located in the city of Esmeraldas, Ecuador. The instrument used for data collection was an in-depth interview with 41questions based on the model of Hayes et al.(2006). The results have shown the effort, wear and tear experienced by teachers in the face of the new demands of reality and their concern about risk factors that their students have faced during the pandemic, such as difficulties with connectivity and access to technology, the low level of digital skills, the lack of ethics and personal maturity and the complex personal and family reality of many of them, that have placed them in a context of vulnerability and detriment in the quality of the Learning.